2014
DOI: 10.1155/2014/802481
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia Caused by Eggerthella lenta in an Elderly Man with a Gastrointestinal Malignancy: A Case Report

Abstract: Eggerthella lenta is normally found in the digestive tract, but can cause systemic infections in patients with disrupted mucosal lining due to gastrointestinal diseases or in patients with a compromised immune system. This article describes an 86-year-old man with a systemic E lenta infection that was eventually traced to a gastrointestinal cancer. The authors highlight the high mortality rate associated with this infection and the importance of determining the source of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…enriched in the migraine group have been reported to be correlated with solid tissue inflammation (Elsayed and Zhang, 2004b), infection (Finegold et al, 2005), and bacteremia (Elsayed and Zhang, 2004a). E. lenta and F. plautii can cause bacteremia (Wong et al, 2014) and bloodstream infection (Berger et al, 2018), respectively. R. gnavus, which degrades mucin (Crost et al, FIGURE 1 | Reduced gut microbial diversity in migraineurs.…”
Section: Differences Of the Gut Microbiome Between Two Groupsmentioning
confidence: 99%
“…enriched in the migraine group have been reported to be correlated with solid tissue inflammation (Elsayed and Zhang, 2004b), infection (Finegold et al, 2005), and bacteremia (Elsayed and Zhang, 2004a). E. lenta and F. plautii can cause bacteremia (Wong et al, 2014) and bloodstream infection (Berger et al, 2018), respectively. R. gnavus, which degrades mucin (Crost et al, FIGURE 1 | Reduced gut microbial diversity in migraineurs.…”
Section: Differences Of the Gut Microbiome Between Two Groupsmentioning
confidence: 99%
“…Recent reports have shown that several E. lenta infections were associated with the use of intrauterine devices, spondylodiscitis, female genital tract infections, cutaneous abscesses, and bacteremia (in Crohn's disease patients) [1][2][3][4]12]. These data emphasize the importance of further investigation for bacterial virulence factors.…”
Section: Discussionmentioning
confidence: 86%
“…Predisposing conditions include gastrointestinal tract disease, malignancies, hepatobiliary disease, immobilization, bedsores, diabetes mellitus, and stroke [2][3][4]. E. lenta is an emerging pathogen that has been under-recognized because of difficulties with its laboratory identification [3].…”
Section: Introductionmentioning
confidence: 99%
“…The color bar and the right y-axis indicate the relation between the color of the peak and its intensity, in arbitrary units. Displayed species are indicated on the left pathologies, bacteremia complicated by spondylodiscitis, psoas abscess, and meningitis (Gardiner et al, 2015;Gardiner, Korman, & Junckerstorff, 2014;Wong, Aoki, & Rubinstein, 2014). We herein describe the new genus Raoultibacter gen. nov. within the family Eggerthellaceae using the taxono-genomic approach (Fournier & Drancourt, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This family contains the type genus Eggerthella and the genera Adlercreutzia , Asaccharobacter , Cryptobacterium , Denitrobacterium , Enterorhabdus , Gordonibacter , Paraeggerthella , Enteroscipio , Rubneribacter , and Slackia (Gupta et al, ). Among its members, Eggerthella lenta is commonly detected in humans and has been associated with bacteremia in patients with intraabdominal or gastrointestinal tract pathologies, bacteremia complicated by spondylodiscitis, psoas abscess, and meningitis (Gardiner et al, ; Gardiner, Korman, & Junckerstorff, ; Wong, Aoki, & Rubinstein, ). We herein describe the new genus Raoultibacter gen. nov. within the family Eggerthellaceae using the taxono‐genomic approach (Fournier & Drancourt, ).…”
Section: Introductionmentioning
confidence: 99%